Marketing Strategy for Honda Motorcycles at PT. Anugrah Kirana Motor City of Bengkulu - Yessinia Febiola Nainggolan; Tito Irwanto; Iswidana Utama Putra (Penerbit Jurnal Indonesia, 2022)
The research objective was to determine the marketing strategy for Honda motorcycles at PT. Anugerah Kirana Motor, Bengkulu City. The type of research used by the author is qualitative research. The analytical method used in this research is SWOT analysis. The results showed that the company's internal factors consisted of the company's strengths and weaknesses with a total score of each factor that could be broken down into strengths (strengths) owned by PT. The Kirana Motor Award for the City of Bengkulu is 2.84 and the weaknesses are 1.36, so the internal cell of the business factor is 2.84 - 1.36 = 1.48. The company's external factors consist of the company's opportunities and threats with details of the opportunities that the strategy has at 2.2 and for threats it is 1.8, then the external factor cell is 2.2 – 1.8 = 0.4, so it is in cell I in SWOT analysis diagram cell. This indicates that PT. Anugerah Kirana Motor, Bengkulu City, can respond to existing opportunities in an extraordinary way and avoid threats that are in its industrial market.